Free and Open Indo-Pacific in Defense Cooperation between Indonesia and Australia - Soedarman, Yoedhi Swastanto; Pramono, Budi; Mhd Halkis (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Indonesia and Australia are two neighboring countries with different cultural characteristics and patterns of international relations. This research aims to formulate a pattern of strategic partnerships between Indonesia and Australia in the field of defense cooperation. Through the symbolic interactional approach, the researcher saw actors’ behavior between countries by collecting data from various sources; online newspapers, scientific articles, interviews, and discussions illustrated the pattern of defense cooperation between Indonesia and Australia at three levels. At the multilateral level, the relationship between Australia and Indonesia looks rather difficult to reciprocate. At the regional level, especially in the Southeast Asia region, Indonesia and Australia cooperation in non-binding control, and on the bilateral level Indonesia and Australia as equal partners are equally committed to mutual control. Free and Open Indo-Pacific strengthens Indonesia-Australia cooperation in the trade sector. An agreement has been built and ratified into the Indonesia-Australia Law comprehensive economic partnership agreement (IA-CEPA). Thus the internal politics of the alliance is very dynamic. On the one hand, the United States strengthens its dominance by utilizing regional countries challenging Chinese policies as bilateral partnerships. On the other hand, multilateral allies help each other. Development between border countries in various ways for defense development.